Cryptic diversity: Two morphologically similar species of invasive apple snail in Peninsular Malaysia - Rama Rao, Suganiya *; Liew, Thor Seng; Yow, Yoon Yen *; Ratnayeke, Shyamala * (PLOS, 2018)
Invasive snails in the genus Pomacea have spread across Southeast Asia including Peninsular Malaysia. Their effects on natural and agricultural wetlands are appreciable, but species-specific effects are less clear because of morphological similarity among the species. Our objective was to establish diagnostic characteristics of Pomacea species in Malaysia using genetic and morphological criteria. The mitochondrial COI gene of 52 adult snails from eight localities in Peninsular Malaysia was amplified, sequenced, and analysed to verify species and phylogenetic relationships. Shells were compared using geometric morphometric and covariance analyses. Two monophyletic taxa, P. canaliculata and P. maculata, occurred in our samples. The mean ratio of shell height: aperture height (P = 0.042) and shell height: shell width (P = 0.007) was smaller in P. maculata. P. maculata co-occurred with P. canaliculata in five localities, but samples from three localities contained only P.canaliculata. This study is the first to confirm the presence of two of the most invasive species of Pomacea in Peninsular Malaysia using a molecular technique. P. canaliculata appears to be the more widespread species. Despite statistical differences, both quantitative and qualitative morphological characteristics demonstrated much interspecific overlap and intraspecific variability; thus, shell morphology alone cannot reliably verify species identity. Molecular techniques for distinguishing between these two highly invasive Pomacea species are needed to understand their specific ecological niches and to develop effective protocols for their management.